2020
DOI: 10.1002/ctpp.202000070
|View full text |Cite
|
Sign up to set email alerts
|

Ni, Ti, and NiTi laser ablation in vacuum and in water to deposit thin films or to generate nanoparticles in solution

Abstract: An ns Nd:YAG pulsed laser was used to deposit thin films in a vacuum and to generate nanoparticles in the water of Ni, Ti, and NiTi alloys. Laser ablation was measured in terms of removing mass per laser pulse. The laser-generated plasma in vacuum was characterized in terms of temperature and energy of emitted particles. The ablation in water produces nanoparticles with dimensions of the order of 25 nm and solutions with concentrations of the order of some mg/ml. The NiTi alloy stoichiometry is well reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Additionally, the authors showed that applying magnetic field indicates the possibility of controlled particle separation, depending on their size. The morphology of NiNPs obtained via PLAL technique was also reported by Torrisi et al [30]. The NPs were produced for 20 min using the 1064 nm wavelength and it was shown that the concentration decreases with the increased fluence and process duration as the laser light is absorbed in the solution, leading to the partial fragmentation of NPs and hence the reduction in mean size distribution.…”
Section: Introductionsupporting
confidence: 66%
“…Additionally, the authors showed that applying magnetic field indicates the possibility of controlled particle separation, depending on their size. The morphology of NiNPs obtained via PLAL technique was also reported by Torrisi et al [30]. The NPs were produced for 20 min using the 1064 nm wavelength and it was shown that the concentration decreases with the increased fluence and process duration as the laser light is absorbed in the solution, leading to the partial fragmentation of NPs and hence the reduction in mean size distribution.…”
Section: Introductionsupporting
confidence: 66%
“…Although nickel is considered a toxic metal [5], the nickeltitanium alloy is biocompatible due to the high reactivity of titanium in oxygen-saturated environments and the formation of passivated TiO 2 surface layers [6]. The scientific and technical development of the Ti-Ni alloy for biomedical applications is well described [7].…”
Section: Introductionmentioning
confidence: 99%